Partitioning of evapotranspiration using high‐frequency water vapor isotopic measurement over a rice paddy field. Issue 5 (26th May 2015) - Wei, Zhongwang; Yoshimura, Kei; Okazaki, Atsushi; Kim, Wonsik; Liu, Zhongfang; Yokoi, Masaharu
Abstract Partitioning ecosystem evapotranspiration (ET) into soil evaporation (E) and transpiration (T) is crucial for understanding hydrological processes. In this study, by using high‐frequency isotope measurements and continuous surface water measurements, we investigated the isotope ratios in soil‐vegetation‐atmosphere transfer and the physical mechanisms involved over a paddy field for a full growing season. The isotopic signals of δET, δT, and δE were determined by the Keeling plot method, surface water isotopic measurements, and the Craig‐Gordon model, respectively. The fraction of transpiration in evapotranspiration (FT) ranged from 0.2 to 1, with an almost continuous increase in the early growing season and a relatively constant value close to 1 later in the year. The result was supported by FT derived from simulated T and eddy correlation measured ET. The seasonal change in the transpiration fraction could be described quite well as a function of the LAI (FT = 0.67LAI0.25, R2 = 0.80), implying that transpiration plays a dominant role in the soil‐vegetation‐atmosphere continuum during the growing season. The two end‐member uncertainty analysis suggested that further improvement in the estimation of δT and δET is necessary for partitioning evapotranspiration using the isotopic method. In the estimation of δET, the assumptions underlying Keeling plot method were rarely met and the uncertainty was quite large. A high frequency of precise isotopic measurements in surface water was also necessary for δT estimation. Furthermore, special care must be taken concerning the kinetic fractionation parameter in the Craig and Gordon Equation for δE estimation under low‐LAI conditions. The results demonstrated the robustness of using isotope measurements for partitioning evapotranspiration.